STUDY OF THE STRUCTURE OF DENTAL COMPLICATIONS AND THE EFFECTIVENESS OF THEIR PREVENTION IN PATIENTS WITH BREAST CANCER AND LUNG CANCER IN THE ZAPORIZHZHIA REGION - A.M. Filon; O.P. Kolesnik; O.V. Voznyi (Український стоматологічний альманах, 2022)
The aim of the work is to analyze the data of patients with malignant neoplasms of the breast and lungs, to investigate the structure of dental complications before and after chemotherapy, to determine the effectiveness of dental prophylaxis.